Homogenization and Turkification practices in Kuzguncuk, Istanbul in the context of the events of 6-7 September 1955 - Kürküt, Emircan. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2019., 2019)
Kuzguncuk is a small, popular village in Istanbul near the Bosphorus. According to most official and unofficial written and oral documents, Kuzguncuk was a village of mostly Jews, Greeks, and Armenians rather than Muslim Turks up until the mid-twentieth century. In other words, the neighborhood is usually described by residents and in local and official discourses as a village of peace, harmony, and tolerance. Kuzguncuk’s non-Muslim population started to decrease following the Turkification and homogenization practices of the Turkish nation-state such as Turkifying street names (the 1930s), a capital tax (1942), 6-7 September pogrom (1955), the deportation of Greek (1964), and the military operation in Cyprus (1974). Most of the Greeks and Jews were forcibly or voluntarily migrated to Greece and Israel. Specifically, the events of 6-7 September directly damaged Kuzguncuk’s non-Muslims because looters attacked several non-Muslim houses and shops. Unfortunately, recent statistics reveal that the current non- Muslim population of Kuzguncuk is only 1 percent of the total population of the village. Kuzguncuk lost its multicultural characteristic though Muslim Kuzguncuk residents hold up the multiethnic characteristic of the village in their nostalgic discourses. The general objective of this research is to unpack the historical facts of the Turkish Republic’s homogenization and Turkification practices via an analysis of the case of Kuzguncuk. In other words, this study is a memory work of one of the well-known villages of Istanbul.
Keywords: Anti-Greek Riots, Istanbul, Turkey, 1955.